Upstairs for Hebrew, Downstairs for English: The Jewish Community of Ste-Sophie, Quebec and Strategies for Public Education, 1914-1952 - MacLeod, Roderick; Poutanen, Mary Anne (Canadian Jewish Studies / Études juives canadiennes, 2002)
In general, Jews were outsiders with regard to Quebec’s public school system until the 1960s. Few were hired as teachers before the mid-twentieth century, and they could not be elected to school boards. For some years at the beginning of the century, even the very right to schooling was in question for Jewish children. An exception to this outsider status was the rural community of Ste-Sophie. There Jews, who comprised the majority of the non-Catholic residents, succeeded in forming the separate (“Protestant”) school board which maintained just one two-room school that catered to the special needs of Jewish children. The board also looked after other aspects of Jewish life in the community. This paper outlines the history of the school and analyzes the developments that led to its establishment.